From Knowledge to Practice: Strengthening Handwashing with Soap Behaviors among Elementary School Students Through an Interactive School-Based Health Promotion Program in Indonesia - Ottay, Ronald Imanuel; Budiarso, Fona Dwiana Hermina; Sumampouw, Oksfriani Jufri; Nelwan, Jeini Ester; Sumampouw, Jeanneprita Jeksi Yesinta Endarini; Sumampouw, Jeannedria Jeisi Yuniar Eleanor (Komunitas: Hasil Kegiatan Pengabdian Masyarakat Indonesia, 2026)
This community service program aimed to improve students’ knowledge and practical skills regarding proper HWWS at SDN 107 Manado. The program was conducted on September 9, 2025, using a group-based health education approach. Educational activities included interactive lectures, audiovisual media, posters, educational songs, demonstrations, and supervised practice of the six-step handwashing technique recommended by the World Health Organization (WHO). Program evaluation was conducted through observation, interactive questioning, and pretest–posttest assessment of students’ knowledge. Initial observations indicated that many students had limited understanding of the importance of HWWS and were unable to correctly perform the recommended handwashing procedures. Following the intervention, most participants demonstrated improved knowledge and were able to correctly perform the six-step handwashing technique. Students also showed high enthusiasm during practical sessions and actively participated in the learning process. In conclusion, the program effectively enhanced students’ knowledge and handwashing skills, highlighting the importance of interactive school-based health education in promoting healthy behaviors and preventing communicable diseases among elementary school students.